The process of cancer. Part III. Selected vitamins in cancer. Chemoprevention - Sylwia Paulina Jopkiewicz (Kazimierz Wielki University, 2019)
Introduction and objective: Free radicals (ROS), affect the course of each step of the process of carcinogenesis. Antioxidants that interact with ROS inactivates them, resulting in a positive effect both in preventing and inhibiting the progression of cancer. Vitamins such as A, C, E and D have anticancer properties. The article gives an overview of the problems of comp contribution of each vitamin in the chemoprevention of cancer. Its purpose is to present some antioxidants for its potential anti-tumor and to provide modifications to their effect on the carcinogenesis process. Description of knowledge: Vitamin A inhibits inter alia, lipid peroxidation and influences the growth and differentiation of epithelial cells to prevent neoplastic transformation. Vitamin E inhibits inter alia, angiogenesis, growth and proliferation of diseased cells. It also has the ability to stop the cell cycle. It prevents the formation of carcinogenic nitrosamines. Vitamin D inhibitor of vascular endothelial growth factor, and factors stimulating cell proliferation. Suppressive affects COX-2 enzyme. Increases the synthesis of E-cadherin. Vitamin C contributes to the proper functioning of the immune system by stimulating the activity of B and T lymphocytes is an electron donor for protecting cell components against oxidation. Stimulates cells to produce hyaluronidase inhibitor. Induces the synthesis of proteins p73 and MLH1. Conclusions: Imbalance redox system can lead to neoplastic transformation. Taking antioxidant supplements is associated with the risk of delivering them in too large a dose. Consequently, there is a support of the oxidation processes. The best way to protect against cancer and support cancer therapy is to provide antioxidants in their natural form, ie in the form of fresh vegetables and fruits.